Parental perceptions and acceptance of silver diamine fluoride treatment in Kingdom of Saudi Arabia - Alshammari, Abdullah Faraj; Almuqrin, Amjad Ali; Aldakhil, Ahmed Mohammed; Alshammari, Bashayer Hamad; Lopez, Jose Nazareno J. (International Journal of Health Sciences, 2019)
Objectives: Dental caries managed through two main approaches: Treatment and prevention; one of the recently preventive measures is silver diamine fluoride (SDF), which proven to be a cost effective, minimally invasive, and handy. SDF also is a treatment that could be chosen for uncooperative patients to stop active caries. SDF has drawbacks, and one of these is staining, which may raise esthetic concerns. Materials and Methods: This was a cross-sectional study, and the collected data were obtained from Saudi volunteers in Kingdom of Saudi Arabia. Questionnaire designed to obtain demographic data from participants and their opinion about the staining was shown in the photographs after using SDF on primary teeth. Results: Of the 222 participants, when we asked their opinion about the staining, we found that the majority reject this type of treatment. In our analyses, there was statistically significant difference in acceptance ratings between male and female with SDF on posterior teeth (P > 0.05). Conclusion: The majority reject this type of treatment. There was a difference in acceptance to the treatment between anterior and posterior teeth. Dentist should provide informed consent form which includes clear photographs showing expected staining, especially when treating anterior teeth.